PEMBUATAN LAPISAN TIPIS DAN SERBUK TIMBAL TITANAT DENGAN METODA SOL GEL - -, Rahmayeni; -, Emriadi; Susanti, Eli; Silvia, Delfi (Universitas Andalas, 2007)
ABSTRACT Thin layer and powder of lead titanate had been prepared using lead acetate and tetraethylorthotitanate as precursor by sol gel process. The thin layer of composite was obtain through layering the composite on glass substrate. Both thin layer and powder were calcined between 100-700°C and were characterized by Scanning Electron Microscopy (SEM), X-ray diffraction (XRD), UV and Fourier Transform Infra Red (FTIR). The diffraction pattern show that the structure of composite on glass substrate is amorf at 500°C and could not identified at 700°C while the powder is crystalline at 500 and 700°C. FTIR spectra shown the Ti-O peak at 1407 cm-1, the Pb-O and Pb-O-Ti peaks at 718 and 600 cm-1, respectively.